2015
DOI: 10.1038/hortres.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Variations in zonal fruit starch concentrations of apples – a developmental phenomenon or an indication of ripening?

Abstract: Patterns of starch hydrolysis in stem, equatorial, and calyx zones of ‘Honeycrisp’ and ‘Empire’ apples (Malus sylvestris (L.) Mill var. domestica (Borkh.) Mansf.) during maturation and ripening, and in ‘Gala’ apples in response to propylene or 1-methylcyclopropene (1-MCP) treatments after harvest, were studied. Differences in zonal starch concentrations were found for ‘Empire’ and ‘Gala’ fruits, but not for ‘Honeycrisp’. During maturation and ripening of ‘Empire’, the concentration of starch was highest in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
1
30
0
2
Order By: Relevance
“…Starch hydrolysis was highly affected by ethylene production in 'Gala' apples (Doerflinger et al, 2015a). Doerflinger et al (2015b) reported that IEC was positively correlated with SPI over a wide range of fruit maturities for 'Gala', 'Honeycrisp', 'McIntosh', and 'Empire' apples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch hydrolysis was highly affected by ethylene production in 'Gala' apples (Doerflinger et al, 2015a). Doerflinger et al (2015b) reported that IEC was positively correlated with SPI over a wide range of fruit maturities for 'Gala', 'Honeycrisp', 'McIntosh', and 'Empire' apples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preharvest treatment can retain fruit firmness of 'Gamhong' apples during cold storage (Yoo et al, 2013) and of 'Delicious' apples during long-term controlled atmosphere (CA) storage (Elfving et al, 2007). Preharvest 1-MCP treatment did not affect flesh firmness and starch pattern index values (SPIs) of 'Law Rome' apples (McArtney et al, 2009), but it did reduce internal ethylene concentrations (IECs), chlorophyll content (in terms of I AD values), and starch hydrolysis of 'Gala' apples (Doerflinger et al, 2015a). Preharvest 1-MCP applications reduced the incidences of soft scald and soggy breakdown in 'Honeycrisp' apple (DeEll and Ehsani-Moghaddam, 2010) and superficial scald in 'Golden Delicious' apple (McArtney et al, 2008).…”
mentioning
confidence: 99%
“…Starch hydrolysis in apples can be dependent or independent of ethylene concentration, whether exogenous or endogenous (Thammawong and Arakawa, 2007;Doerflinger et al, 2015a). Postharvest 1-MCP effects on starch hydrolysis in apples also can be cultivar-dependent (Fan et al, 1999;Neuwald et al, 2010;Thammawong and Arakawa, 2010;Doerflinger et al, 2015b). In bananas, 1-MCP delays hydrolysis in a dose-and cultivardependent manner (Nascimento et al, 1997;Mainardi et al, 2006).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Neste sentido, a utilização de sacarose como fonte de carbono pode ser alternativa viável para produção de H2. Lima et al (2013) (Doerflinger et al, 2015).…”
Section: Universidade De São Paulounclassified
“…Glicose e frutose também foram observados porTorquato et al (2016) como sendo os principais carboidratos em resíduos frutícolas. Tais açúcares como principais carboidratos de frutas é devido a degradação do amido durante a maturação do fruto, liberando glicose e frutose, que poderá ser utilizado para o metabolismo microbiano(Doerflinger et al, 2015), tornando o processo de hidrólise fator determinante para disponibilização de açúcares solúveis. De acordo comJesus et al (2004) e Chitarra eChitarra (2005) o tipo e a quantidade dos açúcares solúveis se alteram de acordo com as variedades, estádios de maturação e condições de cultivo das bananeiras.O pH ácido no valor de 4,42 mensurado no resíduo pode ser justificado pela presença de ácidos orgânicos provindos da degradação do próprio substrato via fermentação natural.Valor de pH ácido, 3,81, também foi relatado porMenezes et al (2015) na caracterização do resíduo de banana.…”
unclassified